The Tegument Protein pp65 of Human Cytomegalovirus Acts as an Optional Scaffold Protein That Optimizes Protein Uploading into Viral Particles - Reyda, Sabine (American Society for Microbiology, 2014)
The mechanisms that lead to the tegumentation of herpesviral particles are only poorly defined. The phosphoprotein 65 (pp65) is the most abundant constituent of the virion tegument of human cytomegalovirus (HCMV). It is, however, nonessential for virion formation. This seeming discrepancy has not met with a satisfactory explanation regarding the role of pp65 in HCMV particle morphogenesis. Here, we addressed the question of how the overall tegument composition of the HCMV virion depended on pp65 and how the lack of pp65 influenced the packaging of particular tegument proteins. To investigate this, we analyzed the proteomes of pp65-positive (pp65pos) and pp65-negative (pp65neg) virions by label-free quantitative mass spectrometry and determined the relative abundances of tegument proteins. Surprisingly, only pUL35 was elevated in pp65neg virions. As the abundance of pUL35 in the HCMV tegument is low, it is unlikely that it replaced pp65 as a structural component in pp65neg virions. A subset of proteins, including the third most abundant tegument protein, pUL25, as well as pUL43, pUL45, and pUL71, were reduced in pp65neg or pp65low virions, indicating that the packaging of these proteins was related to pp65. The levels of tegument components, like pp28 and the capsid-associated tegument proteins pp150, pUL48, and pUL47, were unaffected by the lack of pp65. Our analyses demonstrate that deletion of pp65 is not compensated for by other viral proteins in the process of virion tegumentation. The results are concordant with a model of pp65 serving as an optional scaffold protein that facilitates protein upload into the outer tegument of HCMV particles. IMPORTANCE The assembly of the tegument of herpesviruses is only poorly understood. Particular proteins, like HCMV pp65, are abundant tegument constituents. pp65 is thus considered to play a major role in tegument assembly in the process of virion morphogenesis. We show here that deletion of the pp65 gene leads to reduced packaging of a subset of viral proteins, indicating that pp65 acts as an optional scaffold protein mediating protein upload into the tegument.